Estudo de propriedades não lineares de compósitos com nanotubos de carbono - Valadão, Daniela Rodrigues Borba (2010)
In this work, we investigate the nonlinear optical properties of composites with carbon nanotubes using the Z-scan technique with laser high repetition rate. Using this technique we determine the value of nonlinear refraction index of the composites, evaluating their thermal and electronic contributions. The composites consist of single-walled carbon nanotubes, disperse in different surfactants (NaDDBS, NaC and organic solvent NMP) with different nanotube concentration. To perform the Z-scan technique, we use as a light source a Ti:Sapphire laser pulsed, delivering pulses of 200 fs, linearly polarized, with 76 MHz repetition rate and turned at 791 nm. The sample exposure was controlled by a chopper with a frequency of 14 Hz. The transmitted light was measured by a photodetector as a function of sample position. The composites analyzed present refractive nonlinear index that increases according to the concentration carbon nanotube. However, these composites doesn’t show nonlinear absorption in the experimental conditions used.